Thermosiphon Monitoring Reel for the Fair-Trade Sustainable Hatcheries - Valdès, Laurent-Charles (Graduate School, Universitas Brawijaya, 2025)
Hatcheries designed to be fair-trade, sustainable, well adapted to sunny countries and operating mainly through thermosiphon flows generated by solar radiation or radiative emission at night, were recently the subject of a theoretical study. The dimensionings of their incubator, solar collector, night and heat discharge radiators, water reserve and chassis for the climatic conditions in Cameroon and Indonesia were deduced from this. However, some secondary but essential functional aspects of the implementation of these hatcheries were not addressed. To facilitate their use and operation, a turbine is used here to check whether the thermosiphon flows take place and what is their intensity. The use of the thermosiphon flow control turbines is proven to give important advantages. Firstly, this design support a more eco-friendly environment by being energy neutral. Secondly, this design uses simple, cheap, and long-lasting materials. As a result, this fair-trade sustainable hatchery represents the environmentally friendly and affordable solution, especially for third world countries such as Cameroon and Indonesia. This will help to realize sustainable development goals, especially SDG 7 (clean and affordable energy).